Overdiagnosis of epithelial abnormalities in atrophic cervical pap smears unmasking overdiagnosis in atrophic pap smears - Fasahath Jahan Uzma; Shilpa L; Prathima S (Medical Laboratory Journal)
Background: Cervical cancer has seen a significant decline in death rates due to early diagnosis and treatment. The Pap test remains valuable but exhibits limitations, such as false positives and false negatives, with the former associated with atrophy-related changes. This article aims to bring attention to cervical carcinoma screening, focusing on the interpretation of atrophy-related changes in Pap smears and minimizing intervention. Methods: This retrospective study, conducted at a tertiary care center, evaluated cases with intra-epithelial abnormalities or malignancies in Pap smears. Results: A total of 11,680 cervical cytology smears received in the Department of Pathology, Vydehi Institute of Medical Sciences and Research Centre, Bengaluru, over 7.5 years (From January 1, 2016, to June 30, 2023), were reviewed. Of these, 56 cases exhibited epithelial abnormalities and were categorized as follows: 1. Atypical squamous cells of undetermined significance, 2. Low-grade squamous intraepithelial lesion, 3. High-grade squamous intraepithelial lesion, and 4. Malignancy. Among the 56 smears, 40 (71%) showed co-existent atrophy. Biopsies were available for 22 smears, and atrophy with epithelial abnormalities co-existed in 16 (28%) of these cases. Of these 16 cases, only eight (50%) were found to have abnormalities greater than Cervical Intraepithelial Neoplasia II dysplasia. This results in the positive predictive value of cervical cytology smears detecting epithelial abnormalities in cases with co-existing atrophy-related changes being only 50%. Conclusion: The article emphasizes the importance of cautious interpretation of Pap smears in the presence of atrophy.